"The Skiver Screw". Issue 7 (July 2015) - Cole, Peter A.; Jamil, Mujahid; Jacobson, Aaron R.; Hill, Brian W.
<x xml:space="preserve">Abstract</x> Summary: The contour of the ilium is curved and the iliac fossa is thin, making adequate fixation for fractures involving the iliac wing challenging to achieve at times. The purpose of this article is to describe a previously unreported technique for enhancing fixation in iliac fractures using simple cortical screws.